Enhancement of neurogenesis and cognition through intranasal co-delivery of galanin receptor 2 (GALR2) and neuropeptide Y receptor 1 (NPY1R) agonists: a potential pharmacological strategy for cognitive dysfunctions. - Sánchez-Varo, Raquel María; López-Salas, Alexander; Rasiel, Beltran-Casanueva; Díaz-Sánchez, Estela; Álvarez-Contino, José Erik; Barbancho-Fernández, Miguel Ángel; Serrano-Castro, Pedro Jesús; Fuxe, Kjell; Borroto Escuela, Dasiel Óscar; García-Casares, Natalia; Narváez-Peláez, Manuel (Springer Nature, 2024)
Background: Spatial memory deficits and reduced neuronal survival contribute to cognitive decline seen in the aging process. Current treatments are limited, emphasizing the need for innovative therapeutic strategies. This research explored the combined effects of intranasally co‑administered galanin receptor 2 (GALR2) and neuropeptide Y1 receptor (NPY1R) agonists, recognized for their neural benefits, on spatial memory, neuronal survival, and differentiation in adult rats. After intranasal co‑delivery of the GALR2 agonist M1145 and a NPY1R agonist to adult rats, spatial memory was tested with the object‑in‑place task 3 weeks later. We examined neuronal survival and differentiation by assessing BrdUIR profiles and doublecortin (DCX) labeled cells, respectively. We also used the GALR2 antagonist M871 to confirm GALR2’s crucial role in promoting cell growth. Results: Co‑administration improved spatial memory and increased the survival rate of mature neurons. The positive effect of GALR2 in cell proliferation was confirmed by the nullifying effects of its antagonist. The treatment boosted DCX‑labeled newborn neurons and altered dendritic morphology, increasing cells with mature dendrites. Conclusions: Our results show that intranasal co‑delivery of GALR2 and NPY1R agonists improves spatial memory, boosts neuronal survival, and influences neuronal differentiation in adult rats. The significant role of GALR2 is emphasized, suggesting new potential therapeutic strategies for cognitive decline.
Keywords: Neurobiología del desarrollo; Sistema nervioso - Degeneración; Sistema nervioso - Regeneración; Neurogenic enhancement; Cognitive enhancement; Intranasal administration; GALR2 agonists; NPY1R agonists; M1145; Spatial memory performance; Neuronal survival; Neuronal differentiation